A tumor-binding antibody with cross-reactivity to viral antigens - Michael J. Campa; Elizabeth B. Gottlin; Kevin Wiehe; Edward F. Patz (Cancer Immunology, Immunotherapy, 2025)
Abstract Background We previously identified in non-small cell lung cancer (NSCLC) patients an autoantibody to complement factor H (CFH) that is associated with non-metastatic disease and longer time to progression in patients with stage I disease. A recombinant human antibody, GT103, was cloned from single B cells isolated from patients with the autoantibody. GT103 inhibits tumor growth and establishes an antitumor microenvironment. The anti-CFH autoantibody and GT103 recognize the epitope PIDNGDIT within the SCR19 domain of CFH. Here, we asked if this autoantibody could have originally arisen as a humoral response to a similar epitope in a viral protein from a prior infection. Methods Homologous viral peptides with high sequence identity to the core PIDNGDIT epitope sequence were identified and synthesized. NSCLC patient plasma containing anti-CFH autoantibodies were assayed by ELISA against these peptides. GT103 was assayed on a 4345-peptide pathogen microarray. Results Epitopes similar to the GT103 epitope are present in several viruses, including human metapneumovirus-1 (HMPV-1) that contains a sequence within attachment glycoprotein G that differs by one amino acid. Anti-CFH autoantibodies in NSCLC patient plasma weakly bound to an HMPV-1 peptide containing the epitope. GT103 cross-reacted with multiple viral epitopes on a peptide microarray, with the top hits being peptides in the human endogenous retrovirus-K polymerase (HERV-K pol) protein and measles hemagglutinin glycoprotein. GT103 bound the viral HMPV-1, HERV-K pol, and measles epitope peptides but with lower affinity compared to the GT103 epitope peptide. Conclusion These findings suggest that memory B cells against a viral target could have affinity matured to produce an antibody that recognizes a similar epitope on tumor cells and exhibits antitumor properties.